HUMAN FACTOR IN THE RUSSIAN ECONOMIC CYCLE - V. A. Shalandin (Russian Journal of Economics and Law)
The article views the issues of the cyclic development of market economy, the features of economic cycle in Russia. The role of human factor and its peculiarity in the Russian economic cycle is defined in particular.